2007
DOI: 10.1007/s00441-007-0390-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of nestin-positive putative mammary stem cells in human breastmilk

Abstract: Stem cells in mammary tissue have been well characterised by using the mammary stem cell marker, cytokeratin (CK) 5 and the mature epithelial markers CK14, CK18 and CK19. As these markers have never been reported in cells from breastmilk, the aim of this study has been to determine whether mammary stem cells are present in expressed human breastmilk. Cultured cells from human breastmilk were studied by using immunofluorescent labelling and reverse transcription/polymerase chain reaction (RT-PCR). We found a he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
97
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(107 citation statements)
references
References 27 publications
8
97
2
Order By: Relevance
“…In addition, the work also demonstrated the expression of certain unique markers of dendritic cells, and of myoepithelial progenitors and of platelet derived growth factor that are responsible for immunity, growth, migration and angiogenesis. Overall, the percentages of expressions of all cell surface markers analysed in our study was found to be much higher than that in earlier reports (Patki et al 2010;Fan et al 2010;Cregan et al 2007). Moreover, there was also a variation seen in the percentage of expression within the twenty-six samples for all markers.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…In addition, the work also demonstrated the expression of certain unique markers of dendritic cells, and of myoepithelial progenitors and of platelet derived growth factor that are responsible for immunity, growth, migration and angiogenesis. Overall, the percentages of expressions of all cell surface markers analysed in our study was found to be much higher than that in earlier reports (Patki et al 2010;Fan et al 2010;Cregan et al 2007). Moreover, there was also a variation seen in the percentage of expression within the twenty-six samples for all markers.…”
Section: Discussioncontrasting
confidence: 93%
“…Regardless of the accumulating evidences on the existence of stem cells in human breast milk (Patki et al 2010;Fan et al 2010;Cregan et al 2007), there seems to be paucity of information pertaining to its cellular constituents. Besides, it was believed that breast milk derived stem cells possess a colossal regenerative potency that can be used for treating a wide horizon of neonatal disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most CD4 + and CD8 + T cells are effector memory cells 7,8 . Up to 6% of breast milk cells are progenitor or stem cells of haemopoietic, mesenchymal and neuroepithelial lineages 9,10 . Some of these cells express markers that suggest a mesenchymal stem cell phenotype (CD90, CD44, CD271 and CD146), some express markers of em bryonic stem cells (TRA-1-60, octamer-binding protein 4 (OCT4), NANOG and SOX2) and some express markers of luminal mammary epithelial cells (cytokeratin 18) 11 .…”
mentioning
confidence: 99%